Жисмоний маданият факультетлари талабаларининг асосий гимнастика воситалари орқали касбий фаолиятини ошириш муаммолари (ILIM hám JÁMIYET, 2022)
The article talks about the increase and development of the professional activity of students of the faculties of physical culture with the help of basic gymnastics.